2021
DOI: 10.3389/fmicb.2021.629793
|View full text |Cite
|
Sign up to set email alerts
|

Effects and Mechanisms of Symbiotic Microbial Combination Agents to Control Tomato Fusarium Crown and Root Rot Disease

Abstract: This study evaluated the effects and underlying mechanisms of different combinations of plant symbiotic microbes, comprising arbuscular mycorrhizal fungi (AMF), plant growth-promoting rhizobacteria (PGPR), and Trichoderma spp., on tomato Fusarium crown and root rot (TFCRR) resistance. A total of 54 treatments were applied in a greenhouse pot experiment to tomato (Solanum lycopersicum) seedlings inoculated with or without Funneliformis mosseae (Fm), Rhizophagus intraradices (Ri), Trichoderma virens l40012 (Tv),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…The combined treatment of AMF and Bacillus has an excellent control effect on plant root diseases. Mixed inoculation of G. mosseae and Bacillus subtilis can not only reduce the severity of tomato fusarium root rot by 85.0–93.4%, but can also improve plant nutrients (nitrogen, phosphorus, potassium, calcium, magnesium, iron, and zinc), leaf pigment, total soluble sugar, total soluble protein, and total free amino acid content [ 50 , 51 ]. Zhang et al [ 52 ] found that G. versiforme and B. vallismortis inoculation alone reduced the disease index of cotton verticillium wilt by 37.7% and 35.7%, respectively, and combined inoculation of the two reduced the disease index by 63.3%.…”
Section: Amf and Beneficial Microorganisms Combine To Control Plant D...mentioning
confidence: 99%
See 1 more Smart Citation
“…The combined treatment of AMF and Bacillus has an excellent control effect on plant root diseases. Mixed inoculation of G. mosseae and Bacillus subtilis can not only reduce the severity of tomato fusarium root rot by 85.0–93.4%, but can also improve plant nutrients (nitrogen, phosphorus, potassium, calcium, magnesium, iron, and zinc), leaf pigment, total soluble sugar, total soluble protein, and total free amino acid content [ 50 , 51 ]. Zhang et al [ 52 ] found that G. versiforme and B. vallismortis inoculation alone reduced the disease index of cotton verticillium wilt by 37.7% and 35.7%, respectively, and combined inoculation of the two reduced the disease index by 63.3%.…”
Section: Amf and Beneficial Microorganisms Combine To Control Plant D...mentioning
confidence: 99%
“…Zhang et al [ 52 ] found that G. versiforme and B. vallismortis inoculation alone reduced the disease index of cotton verticillium wilt by 37.7% and 35.7%, respectively, and combined inoculation of the two reduced the disease index by 63.3%. The combined inoculation of AMF and Bacillus has a control effect of 73.6–82.1% against F. oxysporum [ 51 ], while the control effect of single inoculation is only 34.1–52.1%. In addition, under greenhouse conditions, the control effect of combined inoculation of G. mosseae , G. monosporum , A. laevis , R. clarus , and B. amyloliquefaciens on Allium sativum white rot [ 53 ] is also better than that of single inoculation.…”
Section: Amf and Beneficial Microorganisms Combine To Control Plant D...mentioning
confidence: 99%
“…It had been reported that Trichoderma could control Fusarium crown rot, most of which were T. harzianum 49 51 . We believed that the different effects of Trichoderma on the control of wheat diseases may be related to pathogenic fungi, Trichoderma strains, ecological environment and rhizosphere soil microbial communities.…”
Section: Discussionmentioning
confidence: 99%
“…He et al [ 62 ] indicated that phosphorus-solubilizing bacteria improved the tolerance to cadmium by regulating amino acid, organic acid, and carbon metabolism in Solanum nigrum roots. According to Cai et al [ 63 ], plant rhizosphere growth-promoting bacteria can resist tomato root rot by regulating metabolic components. Our results showed that the alleviation of cucumber Fusarium wilt by the plant rhizosphere growth-promoting strain NSY50 is related to the regulation of central carbon metabolism, amino acids, and other derivative metabolites ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…The inoculation of PGPR will lead to an increased amino acid metabolism, thus hastening plant growth [ 74 , 75 ]. Cai et al [ 63 ] observed that increasing amino acid metabolism played a key role in regulating the tomato plants growth caused by plant rhizosphere growth-promoting bacteria and their resistance to pathogens. Our study revealed that numerous kinds of amino acids, especially glutamic acid, ornithine, cysteine, and glycine, significantly increased under F. oxysporum stress than those of control groups.…”
Section: Discussionmentioning
confidence: 99%